2016
DOI: 10.4049/jimmunol.1600699
|View full text |Cite
|
Sign up to set email alerts
|

Active Caspase-1 Induces Plasma Membrane Pores That Precede Pyroptotic Lysis and Are Blocked by Lanthanides

Abstract: Canonical inflammasome activation induces a caspase-1/gasdermin D (Gsdmd) dependent lytic cell death called pyroptosis which promotes anti-microbial host defense but may contribute to sepsis. The nature of the caspase-1-dependent change in plasma membrane (PM) permeability during pyroptotic progression remains incompletely defined. We assayed propidium2+ (Pro2+) influx kinetics during NLRP3 or Pyrin inflammasome activation in murine bone marrow-derived macrophages (BMDM) as an indicator of this PM permeabiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
125
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(137 citation statements)
references
References 81 publications
10
125
0
Order By: Relevance
“…As such, we could not conclusively determine if IL-1β secretion was an active or passive process during necroptosis. This question of whether IL-1β can be actively secreted from cells after caspase-1 activation remains controversial (20,23,(35)(36)(37). These experiments nonetheless suggested that NLRP3 activation could be cell-intrinsic, because glycine treatment had no effect on mature IL-1β secretion following MLKL activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, we could not conclusively determine if IL-1β secretion was an active or passive process during necroptosis. This question of whether IL-1β can be actively secreted from cells after caspase-1 activation remains controversial (20,23,(35)(36)(37). These experiments nonetheless suggested that NLRP3 activation could be cell-intrinsic, because glycine treatment had no effect on mature IL-1β secretion following MLKL activation.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-1 subsequently cleaves and activates the potent proinflammatory cytokines IL-1β and IL-18 and induces their secretion. Although it has been suggested that cell lysis is required for IL-1β release, it has been reported by a number of groups that mature IL-1β secretion is an active cellular process and can occur in the absence of cell death (20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Thus, in a cell undergoing pyroptosis without sufficient compensatory mechanisms, the membrane rupture likely occurs before significant amounts of propidium can be detected inside the cell. However, caution should be used since propidium is very small and, thus, passes freely through the gasdermin pore[28]. It is therefore formally possible that a cell can repair its membrane to remove the gasdermin pore, as was recently shown during necroptosis[24].…”
Section: Gasdermin D Pores Are the Effectors Of Pyroptosismentioning
confidence: 99%
“…However, since the release of proinflammatory cytokines is also blocked by GSDMD deficiency (Shi et al, 2015), and mice deficient for IL-1R type I, the receptor for both IL-1α and IL-1β are highly resistant to LPS (Joosten et al, 2010), a major role of pyropotosis in sepsis in vivo might still be related to the release of proinflammatory cytokines. The cleavage of GSDMD by caspase-1 may play a role in the release of IL-1β by forming an ion-permeable conduit that can be inhibited by broadly acting channel inhibitors such as lanthanides (La 3+ and Gd 3+ ), before pyroptotic cell death (Russo et al, 2016). Caspase-11 mediated cleavage of pannexin-1 can also trigger the release of intracellular ATP through this non-selective large-pore channel, and the subsequent activation of the purinergic receptor P2X ligand-gated ion channel (P2X7), both critical for caspase-11-mediated pyroptosis (Yang et al, 2015).…”
Section: The Downstream Mechanisms Of Pyroptosismentioning
confidence: 99%